Teacher Training in the Development of Video-Based Learning Media by Using Bandicam Application - Nur Laili; Lutfi Fadillah; Jaenullah; Muhammad Zaini; Tamar Lolishvili (Yayasan Payungi Smart Madani, 2022)
Online learning is a challenge for the world of education with the situation of Indonesia which has thousands of islands. Distance learning has set the education process in the country towards digitalization. But on the other hand, it also creates obstacles. This challenge is also an opportunity for educators about how the use of technology can help bring students to be competent for the 21st century. This article aimed to give training in developing of teachers in using media learning that is bandicam application. The service community used Service Learning (SL) method. It was as a medium for integrating voluntary community services with active reflection which is expected to enrich and strengthen training materials in community development with the use of existing assets and potential. The sample was 30 teachers at Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung. The result showed that Bandicam application is a layer recording utility that is very easy to use. This training can increase the knowledge of teachers in using application features in making learning videos and can improve the skills of teachers in making learning videos using the Bandicam application.